Forest Stewardship Council’s (FSC) certification dispute in Sweden - Agblede, Humphery (2010)
Deforestation and biodiversity loss have become an issue of international concern and all stakeholders of environmental protection are concerned in finding a lasting solution to this problem. One tool that has received a lot of attention among environmental non-governmental organizations is forest certification with the Forest Stewardship Council (FSC) being the frontrunner. In Sweden, majority of the industrial forestland holding is FSC certified and the state sees forest certification as an important tool in contributing to the realization of the government‟s environmental protection goals. Notwithstanding this, FSC certification has recently been criticized by some environmental non-governmental organizations as not being effective and efficient in ensuring responsible forestry practices and protection of biological diversity because of the violations of the FSC standard by forest companies among others.